Dinamika Kontemporer Kewarganegaraan Indonesia (Studi Etnisitas Dalam Pemilihan Bupati Pakpak Bharat) - Boangmanalu, Samadam; Sembiring, Armisella Br (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2022)
AbstractCitizenship is the relationship between the individual and the state. This citizenship shows that citizens have certain rights, duties and responsibilities.. In general, every citizen has full political rights in political activities. Indonesia is a democratic country so every citizen who has citizenship status has the right to participate in political activities. This study aims to analyze the contemporary dynamics of citizenship in Indonesia in the 2020 regional head elections in the Pakpak Bharat Regency. The analytical method used in this research is a descriptive qualitative method with a case study approach model. The results show that voting behavior in the Pakpak Bharat community often negates the sociological approach to choosing someone who can be a nurturing leader. In choosing to build on the element of